Temporal restriction of Cas9 expression improves CRISPR-mediated deletion efficacy and fidelity - Jesse A. Weber; Jonathan F. Lang; Ellie M. Carrell; Mohamad-Gabriel Alameh; Beverly L. Davidson (Elsevier, 2024)
Clinical application of CRISPR-Cas9 technology for large deletions of somatic mutations is inefficient, and methods to improve utility suffer from our inability to rapidly assess mono- vs. biallelic deletions. Here we establish a model system for investigating allelic heterogeneity at the single-cell level and identify indel scarring from non-simultaneous nuclease activity at gRNA cut sites as a major barrier to CRISPR-del efficacy both in vitro and in vivo. We show that non-simultaneous nuclease activity is partially prevented via restriction of CRISPR-Cas9 expression via inducible adeno-associated viruses (AAVs) or lipid nanoparticles (LNPs). Inducible AAV-based expression of CRISPR-del machinery significantly improved mono- and biallelic deletion frequency in vivo, supporting the use of the Xon cassette over traditional constitutively expressing AAV approaches. These data depicting improvements to deletions and insight into allelic heterogeneity after CRISPR-del will inform therapeutic approaches for phenotypes that require either large mono- or biallelic deletions, such as autosomal recessive diseases or where mutant allele-specific gRNAs are not readily available, or in situations where the targeted sequence for excision is located multiple times in a genome.